Example 3 Step by Step explanation class 10th Quadratic equation
Example :- find the roots of the equation 2x2-5x+3 by factorisation.
Solution:-
Step 1:- firstly split the middle term -5x as -2x-3x
[because (-2x)*(-3x)]
Step 2:- Now After splitting middle term, we can write the given equation as
2x2-2x-3x+3 =2x(x-1)-3(x-1)=0
Step 3:- now 2x(x-1)-3(x-1)=0
(2x-3)(x-1)=0
2x-3=0 or x-1=0
Step 4:- So, the value of x for which 2x2-5x+3=0
are the same
i.e, either 2x-3=0 or x-1=0
Step 5:- Now, 2x-3=0 gives x=3/2
And x-1=0 gives x=1
So
x= 3/2
and x= 1 is the solution of the equation.
In other word, 1 and 3/2 are the roots of the equation
2x2-5x+3 =0
![](https://blogger.googleusercontent.com/img/b/R29vZ2xl/AVvXsEj-oS1wsyjsKFjIZ5GnQtTPjCPjdc8TKrJdpIiEvHsrrO7OHB4avRyWkrAfqL43ba3YNT4_85Ir4rpkJlDdAorh7Kmkd9iQyYo4TDBKwoWziAC4WTu4-FbKkXEcmW834Q5l_e14Ua4oZKBH/w640-h480/The%252BQuadratic%252BEquation+SOLUTION.jpg)
Comments
Post a Comment